Association of N-terminal pro-brain natriuretic peptide with contrast-induced acute kidney injury and long-term mortality in patients with heart failure and mid-range ejection fraction: An observation study. Issue 10 (March 2017) - Wang, Kun; Li, Hua-long; Chen, Li-ling; Bei, Wei-jie; Lin, Kai-yang; Smyth, Brendan; Chen, Shi-qun; Guo, Xiao-sheng; Guo, Wei; Liu, Yuan-hui; Chen, Peng-yuan; Chen, Ji-yan; et al.
Abstract : Abstract: The potential value of N-terminal pro-brain natriuretic peptide (NT-proBNP) for contrast-induced acute kidney injury (CI-AKI) in patients with heart failure and mid-range ejection fraction (HFmrEF) is unclear. We investigated whether NT-proBNP is associated with CI-AKI and long-term mortality following elective cardiac catheterization in patients with HFmrEF. A total of 174 consecutive patients with HFmrEF undergoing elective coronary angiography or intervention were enrolled. The primary endpoint was the development of CI-AKI, defined as an absolute increase of ≥0.3 mg/dL or ≥ 50% from baseline serum creatinine with 48 hours after contrast medium exposure. Receiver-operating characteristic curve analysis was conducted, and Youden index was used to determine the best cutoff NT-proBNP value. Multivariable logistic regression and Cox proportional hazards regression analyses were performed to identify the independent risk factors for CI-AKI and long-term mortality, respectively. The incidence of CI-AKI was 12.1%. Patients with CI-AKI had higher NT-proBNP values than those without (4373[1561.9–7470.5] vs 1303[625.2–2482.3], P  = 0.003). Receiver-operating characteristic curve revealed that NT-proBNP was not significantly different from the Mehran risk score in predicting CI-AKI (area under the curve [AUC] = 0.723 vs 0.767, P  = 0.516). The best cutoff NT-proBNP value for CI-AKI was 3299 pg/mL, with 70.6% sensitivity and 83.1% specificity. Multivariable analysis demonstrated that NT-proBNP ≥3299 pg/mL is significantly related to CI-AKI (odds ratio = 12.79; 95% confidence interval, 3.18–51.49; P  < 0.001). Cox regression analysis showed that NT-proBNP ≥3299 pg/mL is associated with long-term mortality (adjusted hazard ratio = 11.91; 95%CI, 2.16–65.70; P  = 0.004) during follow-up. In patients with HFmrEF, NT-proBNP ≥3299 pg/mL is associated with CI-AKI and long-term mortality following elective coronary angiography or intervention.